Re-imagining the nation-state: An impetus from the pandemic - Posocco, Lorenzo; Watson, Iarfhlaith (Frontiers in Sociology, 2023)
In this article the positive lessons from the coronavirus pandemic are examined, focusing on the intensive activities of solidarity at the local, national, and transnational levels, the increase in scientific cooperation, the implementation of assistance policies by states, and the various endeavours of NGOs, religious communities, private organisations, wealthy and less wealthy donors, and charities to support individuals and groups affected by it. It is argued that the pandemic is not only a tragedy that revealed some of the disintegrative processes of global risk society but is also a matchless opportunity for acknowledging what can be (and is) done in the globalised world when guided by positives such as cooperation, coordination, and solidarity. Discussing the theories of globalisation, nationalism, and cosmopolitanism, with special attention to Ulrich Beck’s theory of reflexive society, the core point of this article is that, considering upcoming global threats of even greater magnitude, such as climate change, potentially deadlier pandemics, and nuclear conflicts, a new world order based on cooperation, coordination and solidarity between nation-states is not only desirable but necessary for survival.